Expedient Preparation of Aryllithium and Arylzinc Reagents from Aryl Chlorides Using Lithium 4,4′-Di-tert-Butylbiphenylide and Zinc(II) Chloride - Shen, Zhi-Liang; Sommer, Korbinian; Knochel, Paul (Synthesis, 2015)
We report an efficient method for the preparation of aryllithium and zinc reagents from inexpensive and readily available aryl chlorides by using lithium 4,4′-di-tert-butylbiphenylide (LiDBB) as a lithiation reagent. The resulting organometallic reagents underwent subsequent reactions with a variety of electrophiles, such as an aldehydes, DMF, PhSSO2Ph, TsCN, an aryl halide, or an acid chloride (through Pd-catalyzed cross-coupling). Aryl chlorides bearing substituents, including methoxy, 3,4-methylenedioxy, fluoride, TMS, OTMS, NMe2, acetal, and ketal, were shown to be appropriate substrates. Interestingly, aryl chlorides containing a formyl group could also be used, provided that the formyl group was temporarily converted into an α-amino alkoxide by using the lithium amide of N,N,N′-trimethylethylenediamine (LiTMDA). The presence of a hydroxyl group was also tolerated when it was deprotonated with n-BuLi prior to the addition of LiDBB.
Keywords: organolithium reagents; aryllithium; arylzinc; palladium; cross-coupling